2015
DOI: 10.1515/agri-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

The Energy Effectiveness Of Crops In Crop Rotation Under Different Soil Tillage Systems

Abstract: The paper identifies and compares the energy balance of winter wheat, spring barley and white mustard – all grown in crop rotation under different tillage conditions. The field trial included the conventional tillage (CT) method, minimum tillage (MT) and a system with no tillage (NT). The energy inputs included both the direct and indirect energy component. Energy outputs are evaluated as gross calorific value (gross heating value of phytomass dry matter) of the primary product and the total harvested producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
3
0
4
Order By: Relevance
“…Gross calorific value of the total biomass was 175.35 GJ ha -1 for winter wheat, 149.11 GJ ha -1 for barley and 87.27 GJ ha -1 for white mustard. Winter wheat also had the highest grain and residue yields (Strašil, Vach, & Smutný, 2015).…”
Section: Total Productivity Of Crop Rotations Affected By Included Plmentioning
confidence: 97%
See 1 more Smart Citation
“…Gross calorific value of the total biomass was 175.35 GJ ha -1 for winter wheat, 149.11 GJ ha -1 for barley and 87.27 GJ ha -1 for white mustard. Winter wheat also had the highest grain and residue yields (Strašil, Vach, & Smutný, 2015).…”
Section: Total Productivity Of Crop Rotations Affected By Included Plmentioning
confidence: 97%
“…Energy difference between the energy output and the energy input (both direct and indirect) is called net energy, and it has been studied extensively in the world. Besides, energy intensity (yield against energy input) and energy ratio (output energy against input energy) are also widely studied (Hülsbergen, Feil, & Diepenbrock, 2002;Zentner et al, 2004;Strašil, Vach, & Smutný, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Саме такий підхід застосовують у біологічному землеробстві. Зменшення навантаження на агроекосистему шляхом мінімізіції або припинення застосування хімічних методів захисту рослин також зменшує витрати пального, економічні витрати, витрати людської праці, зношування техніки, що, у свою чергу, зменшує енерговитрати під час вирощування сільськогосподарських культур (Pimentel et al, 1983;Strašil et al, 2015;Tinde et al, 2017).…”
Section: житомирський національний агроекологічний університет житомunclassified
“…It is reported that one of the main reasons why farmers do not want to grow pulses is unstable and more variable yield in comparison to non-legume crops in Europe (Cernay et al, 2015). Traditional soil tillage helps to limit harmful organisms like wheat leaf diseases (Bankina et al, 2018) and weeds (Ausmane, Melngalvis, & Ruža, 2017), but is more time and energy consuming if compared to minimum soil tillage treatments (Strašil, Vach, & Smutný, 2015). In different studies, contradictory results are reported on advantages of soil tillage method (traditional or reduced) to ensure a higher yield and/or quality of wheat (e.g.…”
Section: Introductionmentioning
confidence: 99%